2020
DOI: 10.2196/17589
|View full text |Cite
|
Sign up to set email alerts
|

Development of “Advancing People of Color in Clinical Trials Now!”: Web-Based Randomized Controlled Trial Protocol

Abstract: Background Participation in clinical trials among people of color remains low, compared with white subjects. This protocol describes the development of “Advancing People of Color in Clinical Trials Now!” (ACT Now!), a culturally tailored website designed to influence clinical trial decision making among people of color. Objective This cluster randomized study aims to test the efficacy of a culturally tailored website to increase literacy, self-efficacy,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…However, journals’ websites did not explicitly state when these policies were put into place. Articles reporting stakeholder involvement in trial design were less likely to enroll a diverse population in single-state studies; this finding may have been associated with the encouragement of greater representation of participants of racial and ethnic minority groups, which in turn may have led to lower diversity indexes.…”
Section: Discussionsupporting
confidence: 90%
“…However, journals’ websites did not explicitly state when these policies were put into place. Articles reporting stakeholder involvement in trial design were less likely to enroll a diverse population in single-state studies; this finding may have been associated with the encouragement of greater representation of participants of racial and ethnic minority groups, which in turn may have led to lower diversity indexes.…”
Section: Discussionsupporting
confidence: 90%
“…Participants’ rights and safety, as well as the process and procedures of clinical trial research, funding, setting and benefits, were identified as critical areas to ensure patient understanding. These topic areas were agreed upon as survey items to include in the CHEKS tool given the historical mistrust of research and typical misconception of clinical trials only being pharmaceutical in nature [ 11 , 12 , 26 ]. Our approach is consistent with the literature, with our patient-centered input to the instrument development for key content areas guided by the literature, literacy level and cultural appropriateness guided by the CSC, data collection, troubleshooting user access processes, and survey ease of use administered online.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, our measure could be used as part of pre/posttest research analysis to determine how the research community is faring in improving recruitment and participation in trials from all communities. Examples of such interventions include the development of a tailored website to increase participant willingness to enroll in clinical trials [ 11 ], to understand knowledge content areas to bolster and beliefs or misconceptions to clarify.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In sum, a decentralized clinical trial can address the knowledge, access, and navigation limitations of traditional centralized clinical trials [14][15][16][17][18][19][20]. Decentralized trials have demonstrated value in enhancing participant diversity, recruitment, and retention rates and providing more representative real-world data for improved generalizability of study findings [20].…”
Section: The Value Of Decentralized Trialsmentioning
confidence: 99%